High performance nano-zirconium silicate adsorbent for efficient removal of copper (II), cadmium (II) and lead (II). Issue 2 (June 2015) - Mahmoud, Mohamed E.; Nabil, Gehan M.; Mahmoud, Sarah M.E.
Graphical abstract